Minding the Gap : Writing across Thresholds and Fault Lines. - Conroy, Thom (Cambridge Scholars Publishing, 2015)
"Passengers on the British railway and underground must 'mind the gap'because it's dangerous not to. In a state of embarking or disembarking, passengers must stay aware of the small but significant space separating the stationary from the moving. The contemporary practices of writing and reading are in constant motion, and the phrase 'mind the gap'captures an essential aspect of the way language and literature progress as they pass through any number of social, technical, and political exchanges. 'Minding the gap'also suggests an awareness of the always shifting distance between the expected and the unexpected, the ordinary and the impossible, the familiar and unimagined. This book includes chapters on writing non-fiction, media and genre, and also addresses elements of identity, culture and linguistics in fiction, poetry and creative non-fiction as contributors consider the gaps that exist between the self as writer, as reader and as editor or mentor. The volume adopts the following key themes: new gaps for creative writing in the academy; writing in new genres, media and forms; exploring the creative process and narrative strategies across disciplines. This book will be of international appeal to all readers interested in the changing landscape of creative writing"--EbscoHost.